PENINGKATAN PERAN MASYARAKAT DALAM SYIAR ISLAM MELALUI ADZAN DI MASJID NURUL HIDAYAH DI DESA PEDATARAN GELUMBANG MUARA ENIM - Hendri Hendri; Armasito Armasito (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to examine the forms of community involvement, the impact of the Adzan Magrib activity, and the supporting and inhibiting factors in its implementation in Pedataran Village, Gelumbang, Muara Enim. The research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews with religious leaders, mosque administrators, parents, and documentation of activities. The findings show that community involvement is reflected in parents guiding their children to the mosque, the role of religious teachers in teaching Qur’an reading and moral values, and the support of mosque administrators and the surrounding community in maintaining the activity. The Adzan Magrib activity improves children’s ability to read the Qur’an, builds the habit of congregational prayer, and shapes positive character. Supporting factors include parental support, active religious leaders, strong social ties, and established religious traditions. Meanwhile, obstacles include parents’ busy schedules, digital entertainment influence, limited facilities, and peer influence. Overall, the Adzan Magrib activity serves as an effective means of strengthening Islamic outreach within the Pedataran Village community.